2012
DOI: 10.1124/mol.112.078253
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Blockers Act through Nuclear Factor Y to Control Transcription of Key Cardiac Genes

Abstract: First-generation calcium channel blockers such as verapamil are a widely used class of antihypertensive drugs that block L-type calcium channels. We recently discovered that they also reduce cardiac expression of proapoptotic thioredoxin-interacting protein (TXNIP), suggesting that they may have unappreciated transcriptional effects. By use of TXNIP promoter deletion and mutation studies, we found that a CCAAT element was mediating verapamil-induced transcriptional repression and identified nuclear factor Y (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 52 publications
3
17
0
Order By: Relevance
“…It has been demonstrated that verapamil, when administered to mice through the drinking water at an average dose of 100 mg/kg/day, decreased diabetes-induced cardiomyocyte apoptosis, an effect specifically due its potent inhibition of TXNIP expression (19). Additionally, verapamil enhanced ␤-cell survival and function through its reduction of ␤-cell TXNIP expression (42), and this may be due to verapamil-induced transcriptional repression of TXNIP (43). In the present study, verapamil, at a dose of 50 M, strongly inhibited TXNIP expression in podocytes (data not shown), inhibited TXNIP binding to NLRP3, and prevented Hcys-induced NLRP3 inflammasome formation and activation in podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that verapamil, when administered to mice through the drinking water at an average dose of 100 mg/kg/day, decreased diabetes-induced cardiomyocyte apoptosis, an effect specifically due its potent inhibition of TXNIP expression (19). Additionally, verapamil enhanced ␤-cell survival and function through its reduction of ␤-cell TXNIP expression (42), and this may be due to verapamil-induced transcriptional repression of TXNIP (43). In the present study, verapamil, at a dose of 50 M, strongly inhibited TXNIP expression in podocytes (data not shown), inhibited TXNIP binding to NLRP3, and prevented Hcys-induced NLRP3 inflammasome formation and activation in podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that verapamil may not downregulate TXNIP expression in adipose, liver and muscle and thus, has no effect on insulin sensitivity of these tissues. Apart from β-cells, verapamil had been shown to inhibit TXNIP expression in H9C2 cells and primary adult cardiomyocytes but verapamil effect on TXNIP expression in other cell types is not known [ 99 ]. Allopurinol, a drug used to treat gout and hyperuricemia also reduces TXNIP levels in animals and cultured cells.…”
Section: Txnip Is a Potential Therapeutic Targetmentioning
confidence: 99%
“…And generally, two CCAAT boxes were found in Txnip promoter sequences from different species, which could recruit nuclear factor Y (NF‐Y) to the Txnip promoter. Not only that, the occupancy of the Txnip promoter by NF‐Y might be a prerequisite for efficacious recruitment of Mondo/MLX to ChoREs [28]. Checking the sequences of Txnip‐4 promoter from Chinese hamster, several regulatory elements were illustrated in this region, as shown in Figure 6, such as tandem ChoREs (ChoRE‐a and ChoRE‐b), FOXO, two CCAAT motifs, and TATA box.…”
Section: Discussionmentioning
confidence: 99%